The effect of sugar cane waste product fermented by Pleurotus ostreatus on the ration to Priangan sheep performance - Tarmidi, Ana Rochana (Indonesian Journal of Animal and Veterinary Sciences, 2004)
Bagasse from Saccharum officinarum has potency as roughage source for ruminants. The objective of this research was to evaluate the use of bagasse fermented by Pleurotus ostreatus (ATB) to feed consumption, daily gain and feed efficiency of Priangan sheep. The research was arranged into two stages, i.e: (i) bioconversion of bagasse by P. ostreatus, and (ii) biological test using ATB. Twenty five heads of male Priangan sheep with average body weight of 18.99 + 0.22 kg were fed with ATB for three months. A completely randomized design was carried out with five replications. The treatment were: R0= 70.0% King grass + 30.0% concentrate; R1= 59.50% King grass + 10.10% ATB + 30% concentrate; R2= 49.00% King grass + 21.10% ATB + 30% concentrate; R3= 38.50% King grass + 31.50% ATB + 30% concentrates, and R4= 28.00% King grass + 42% ATB + 30% concentrate. The results of the experiment showed that bagasse fermented by P. ostreatus (ATB) did not indicate negative effects on feed consumption, daily gain, and feed efficiency of Priangan sheep, and ATB can be used as ingredient of Priangan sheep ration up to 31.50% based on dry matter of the ration. Â  Key words: Bagasse, Pleurotus ostreatus, feed consumption, daily gain, feed efficiency